Learning to be innovative in a competitive world - White, David (Mednarodno inovativno poslovanje, 2009)
It is our capacity to turn human creativity into innovation that accounts for economic progress. Our capacity to innovate will be a determinant of the depthand endurance of the economic crisis and how we come out of it. Educationand training can help or hinder this. The positive agenda is well known but challenging. An understanding of how discourse and its interpretation leads towards innovation helps clarify the process and how education and training can help. The paper develops ideas inspired in particular by Paul Ricoeur.
Keywords: creativity; discourse; education; ekonomski napredek; innovation; inovacije; inovacijski proces; inovativna družba; inovativnost; interpretation; izobraževanje; kreativnost; language; surplus of meaning